ANALISIS IMPLEMENTASI ADAPTIVE GOVERNANCE DALAM MENINGKATKAN KINERJA ASN DI KANTOR KECAMATAN MEDAN TIMUR - Claudia Evelyn; Vera Pasaribu; Natalia Sihombing (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The development of the digital era requires government institutions to adapt their bureaucratic work systems and public services to become more effective and responsive. However, the adaptation process still faces several challenges, such as limited technological competence, conventional bureaucratic work patterns, and the readiness of civil servants to face change. Therefore, an adaptive governance approach is needed to encourage flexibility and the ability of organizations to adjust to environmental dynamics. This study aims to analyze the implementation of adaptive governance in improving the performance of civil servants at the Medan Timur Sub-district Office and to identify supporting and inhibiting factors. This research uses a qualitative method with a descriptive approach through interviews and documentation studies. Data analysis applies the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that the implementation of adaptive governance is reflected in collaboration among employees, flexibility in work procedures, improvement of civil servants’ capacity in the use of technology, and the role of transformational leadership in encouraging openness to change. These efforts contribute to improving work effectiveness and the quality of public services. However, several obstacles remain, including limited digital skills, lack of technical training, and work habits that are still oriented toward manual systems. The study concludes that adaptive governance plays an important role in improving civil servant performance and supporting organizational adaptation to the digital transformation of public services.